Conocimientos, actitudes y prácticas sobre enfermedades zoonóticas en Chuquisaca, Bolivia - Méndez, Dennis (2025)
Introduction. About 60% of emerging infectious diseases are zoonotic, originating mainly from wildlife. Objective. To identify knowledge, attitudes, and practices associated with zoonotic transmission risks in communities in urban, rural, and protected areas to prevent potential zoonotic outbreaks. Methods. Cross-sectional study in a representative sample stratified by zones (urban, rural and protected areas) and age groups. A standardized questionnaire in Spanish and Quechua, adapted to the local context, was applied to explore sociodemographic data, contact with animals, attitudes towards wildlife, their trade and consumption, and knowledge about zoonotic diseases and sources of information. Trained local interviewers visited households and recorded information using the ODK application on electronic tablets. Frequencies were described and the chi-square test was used to compare the distribution by area. Results. A total of 922 people participated. Rabies was recognized in the highest percentage (57.3%), Chagas disease (36.1%) and yellow fever (11.5%). Few participants had previous training on zoonosis (8.9%), the majority in the protected area (13.5%). There was concern about zoonosis outbreaks (70.7%), and (70.7%) indicated that wild animals should be protected, significantly different between study areas. (76.4%) have close contact with animals; (62.5%) handle some of them freshly slaughtered; (35.2%) noted the presence of animal feces in or near food; (13.3%) indicated selling, ingesting or sharing dead animals collected from animals. Conclusions. Low knowledge, perceptions, and practices of high zoonotic risk in human-animal interactions were identified, significantly different between areas of residence.